Comprehensive Review of Strengths and Weaknesses of Solar-Biomass Hybrid Power Systems: A Systematic Literature Approach - Setiabudi, Fitri; Nur, Muhammad Syukri; Uyun, Aep Saepul; Lasman, As Natio (Universitas Nasional, 2025)
Solar-biomass hybrid power systems (SBHPS) offer a promising solution to global energy and climate challenges by integrating two complementary renewable sources. This study presents a systematic literature review (SLR) based on 543 articles retrieved from Scopus and Web of Science (2014 to 2024), with 76 full texts screened, 26 meeting the inclusion criteria, and 18 scoring ≥4/5 in quality based on CASP and MMAT frameworks. The analysis identifies key advantages of SBHPS, including improved energy efficiency, supply reliability, greenhouse gas emission reduction, and local resource utilization. Conversely, barriers include high capital costs, resource dependency, technical complexity, and policy constraints. The novelty of this review lies in its integrated, multi dimensional synthesis across technical, economic, environmental, and social aspects, filling a gap left by earlier SBHPS reviews. The findings offer practical insights for energy planners, technology developers, and policymakers aiming to implement sustainable and regionally adapted hybrid systems